Development of an ISMS Maintenance Tracking System for Security Firms in Nairobi County - Muchiri, Esther Wambui; Kinoti, Patrick; Charo, Joel (International Journal of Professional Practice, 2026)
The increasing reliance on integrated security technologies in Kenya’s private security sector has intensified the need for effective maintenance of Integrated Security Management Systems (ISMS) to ensure operational continuity, compliance, and resilience. This study examined current ISMS maintenance practices, identified recognized best practices, and developed a digital ISMS Maintenance Tracking System tailored for private security firms in Nairobi County. Guided by the Design Science Research (DSR) paradigm and theoretically grounded in General Systems Theory (GST), the Technology Acceptance Model (TAM), and Total Productive Maintenance (TPM), the research followed a two-phase process, including a diagnostic quantitative survey to assess existing and best ISMS maintenance practices and the design, development, and validation of an ISMS Maintenance Tracking System via User Acceptance Testing (UAT). Using a descriptive and developmental research design, structured questionnaires were administered to 90 sample respondents, yielding a 70% response rate. Data were analyzed descriptively and inferentially. Results show that current maintenance practices are weak and negatively associated with system effectiveness (B = -0.893, p < 0.001; R² = 0.423), while best practices, including preventive scheduling, SLA monitoring, and real-time logging, positively predict effectiveness (B = 0.815, p < 0.001; R² = 0.350). The combined model (F(2,60) = 89.812, p < 0.001; R² = 0.750) explains 75% of the variance in effectiveness. UAT demonstrated high usability and functionality (over 90% satisfaction across modules). The study concludes that replacing fragmented, reactive procedures with an automated, standards-aligned tracking system substantially improves ISMS reliability, accountability, and compliance. The study recommends adopting ISO/IEC 27001-aligned maintenance frameworks and deploying the developed system in phases. In practice, the study provides a validated maintenance tool; for policy, it offers evidence to inform regulatory frameworks; and theoretically, it extends DSR applications to context-driven ISMS solutions that support Kenya’s Private Security Regulation Act (2016) and SDG 9.